Computer modelling, design and analysis of piezoresistive MEMS accelerometer for concrete SHM applications - Kavitha, S.; Daniel, R. Joseph; Jeyasehar, C. Antony; Sumangala, K. (Journal of Structural Engineering, 2024)
Structural Health Monitoring (SHM) using non destructive testing generally involves measurement of shift in natural frequency of the monitored structure. Vibration sensors play a crucial role in such SHM systems and the present day SHM systems use commercially available off the shelf MEMS accelerometers. In this work, an attempt has been made to design a MEMS accelerometer that is specifically intended for concrete SHM applications. This paper presents the design methodology of a MEMS silicon piezoresistive single axis accelerometer with the seismic mass (m) suspended by four symmetrical cantilever beams. The simulation and analysis results using IntelliSuite MEMS design tool show that this newly designed accelerometer is capable of measuring vibrations up to 2g with a sensitivity of 0.751 mV/g /V in the main axis and less than 20 % of this sensitivity in other axes. The modal analysis results indicate that the designed accelerometer has its first mode natural frequency of 782 Hz against the specifi ed 700 Hz.